Redox and Ionic Homeostasis Regulations against Oxidative, Salinity and Drought Stress in Wheat (A Systems Biology Approach) - Shah, Zahid Hussain; Rehman, Hafiz M.; Akhtar, Tasneem; Daur, Ihsanullah; Nawaz, Muhammad A.; Ahmad, Muhammad Q.; Rana, Iqrar A.; Atif, Rana M.; Yang, Seung H.; Chung, Gyuhwa (Frontiers in Genetics, 2017)
Systems biology and omics has provided a comprehensive understanding about the dynamics of the genome, metabolome, transcriptome, and proteome under stress. In wheat, abiotic stresses trigger specific networks of pathways involved in redox and ionic homeostasis as well as osmotic balance. These networks are considerably more complicated than those in model plants, and therefore, counter models are proposed by unifying the approaches of omics and stress systems biology. Furthermore, crosstalk among these pathways is monitored by the regulation and streaming of transcripts and genes. In this review, we discuss systems biology and omics as a promising tool to study responses to oxidative, salinity, and drought stress in wheat